Characterizing seasonal fishing patterns and growth dynamics during the Middle and Late Holocene in the Strait of Magellan (Chilean Patagonia): Sclerochronological analysis of tadpole codling (Salilota australis) vertebrae - Torres Elgueta, Jimena Andrea; Mahe, K.; Dufour, J. L.; Bearez, P.; San Roman Bontes, Manuel Julio (My University, 2022)
We describe sclerochronological analyses of tadpole codling (Salilota australis) vertebrae as a proxy for the seasonal timing of fishing activities at one Middle Holocene (6500 BP) and three Late-Middle Holocene (3500-2500 years BP) archaeological sites located in Seno Otway and in the central zone of the Strait of Magellan, Chile. These data provide an approximation of the population characteristics of the species in the past by estimating the relationship between size and age of the archaeological fish and comparing their growth rate to those of modern specimens captured monthly over one year. The results showed that the size at age was significantly larger in archaeological samples than in the modern reference collection. Our results indicate that fishing activities took place throughout the year at the Late Holocene sites, with a special emphasis on the cold season, while the Middle Holocene site showed a tendency to catch tadpole codling during the warm season.
Keywords: patagonia; prehistoric fishing; sclerochronology; seasonality; ichthyoarchaeology; fish growth